Where Did All the Aid Go? An Empirical Analysis of Absorption and Spending - Aiyar, Shekhar (International Monetary Fund, 2008)
This paper examines the macroeconomic usage of aid using panel data for a broad sample of aid-recipients. By definition an increase in aid must go toward a reduction in the current account balance (absorbed aid), an increase in capital outflows, or reserve accumulation. It is found that short-run absorption is typically very low, with much aid exiting through the capital account. Moreover, aid spending, defined in terms of the increase in government fiscal expenditures as a result of aid, is significantly greater than aid absorption, implying that aid systematically leads to an injection of domestic liquidity in recipient economies. The evidence here may help illuminate the rather weak link between aid and growth found in the literature. It reinforces the case for greater coordination between fiscal and monetary authorities in response to aid inflows